Not Waving, Drowning: Can Local Government Policies on Climate Change Adaptation and Disaster Resilience Make a Difference?. Issue 3 (3rd July 2017) - Torabi, Elnaz; Dedekorkut-Howes, Aysin; Howes, Michael
Abstract: Climate change will increase the intensity, duration and/or frequency of some climate-related hazards. Responsibility for adapting to such impacts of climate change in Australia has, in the main, fallen on local governments which have paid varying degrees of attention to the issue. This paper takes an integrated approach to compare the climate adaptation and disaster resilience policies and plans of local governments of two low-lying coastal cities in Australia to understand whether (and how) local governments can make a difference. The findings indicate that local governments can significantly contribute to building resilience and adapting to climate-related hazards, however a number of factors such as the attitudes of local governments on climate change, environmental activism, and the recent experiences of climate-related disasters are instrumental for shaping a better local response. Local action also needs to be supported by a more integrated approach by all levels of government.